Akansha Agarwal Revisiting the debate: Legalisation and decriminalization of Prostitution - Agarwal, Akansha (INTERNATIONAL JOURNAL OF SOCIAL, POLICY AND LAW, 2024)
This article explores the complex issue of legalizing and decriminalizing prostitution, drawing from the perspectives of Alexander Kollantai and feminist historical backgrounds. It traces the roots of prostitution in India, particularly affecting vulnerable populations, and examines the ongoing debate between radical feminists and proponents of state involvement. The economic dimensions of the sex industry, the global legal frameworks, and the contrasting approaches in countries like Sweden, the United States, and the Netherlands are analyzed. The role of the state, highlighted by India's legal provisions, is scrutinized alongside the failures in implementing rehabilitation schemes. The article proposes a bottom-up approach, addressing the demand and supply dynamics, creating economic opportunities, and fostering social capital to improve the welfare of women in prostitution. It concludes by advocating for comprehensive strategies involving government and civil societies to combat the multifaceted challenges posed by commercial sexual exploitation.